The definitive guide to the ARM Cortex-M3 - Yiu, Joseph (Newnes/Elsevier, 2010)
This user's guide does far more than simply outline the ARM Cortex-M3 CPU features; it explains step-by-step how to program and implement the processor in real-world designs. It teaches readers how to utilize the complete and thumb instruction sets in order to obtain the best functionality, efficiency, and reuseability. The author, an ARM engineer who helped develop the core, provides many examples and diagrams that aid understanding. Quick reference appendices make locating specific details a snap! Whole chapters are dedicated to: Debugging using the new CoreSight technology Migrating effectively from the ARM7 The Memory Protection Unit Interfaces, Exceptions, Interrupts ... and much more! The only available guide to programming and using the groundbreaking ARM Cortex-M3 processor Easy-to-understand examples, diagrams, quick reference appendices, full instruction and Thumb-2 instruction sets are included€ T teaches end users how to start from the ground up with the M3, and how to migrate from the ARM7.